Pengembangan Media Pembelajaran Interaktif Berbasis Autoplay Media Studio pada Mata Pelajaran PAI dan Budi Pekerti Kelas X di SMAN 1 Batusangkar - Fatma Sari; Eliwatis; Gustina; Romi Maimori (SURAU : Journal of Islamic Education, 2026)
This research is motivated by the use of learning media for Islamic Education (PAI) and Character Education, which is still dominated by PowerPoint, resulting in suboptimal student interaction during the learning process. Although various interactive learning media have been widely developed, the use of Autoplay Media Studio for materials on Avoiding Free Socializing and Adultery remains limited. The novelty of this research lies in the development of interactive learning media based on Autoplay Media Studio, designed according to the characteristics of PAI and Character Education materials to enhance student engagement. This study aims to develop learning media that is valid and practical for grade X high school students. The method used is Research and Development (R&D) with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research was conducted at SMAN 1 Batusangkar, involving three validators—two lecturers and one teacher—as well as six students as practicality test respondents. The results indicate that the developed media obtained a validity score of 0.91, categorized as very valid, and a practicality score of 0.88, categorized as very practical. These findings show that learning media based on Autoplay Media Studio is feasible for use in PAI and Character Education and has the potential to increase student engagement through more interactive material presentation. Thus, this media can serve as an innovative alternative for educators in creating active, effective, and student-centered learning.